EFL Teachers' Classroom Management Orientation, Self-Efficacy, Burnout, and Students' L2 Achievement - Mohammad Hadi Mahmoodi; Shiva Hosseiniyar; Negin Samoudi (Universidad Nacional de Colombia, 2022)
This correlational study examined the relationship among some English teachers' characteristics and their students' foreign language learning. Eighty-two Iranian high school teachers who taught English completed a battery of questionnaires. The scores of the teachers' students on their final exam were collected as indicators of their English achievement. The results revealed that there was a positive relationship between the teachers' self-efficacy, classroom management orientations, personal accomplishments (a subscale of burnout), and students' L2 performance. However, the correlations between emotional exhaustion and depersonalization (two subcomponents of burnout) and students' English learning were negative. Furthermore, the findings indicated that the teachers' self-efficacy was the strongest predictor of learners' English learning. These findings highlight the importance of such teachers' characteristics for their learners' L2 learning.